2006
DOI: 10.1159/000093089
|View full text |Cite
|
Sign up to set email alerts
|

Impaired Endotoxin Tolerance Induction in Patients with Familial Mediterranean Fever

Abstract: Objective: To investigate periodic disturbances in proinflammatory activation of neutrophils and monocytes in patients with familial Mediterranean fever (FMF) both during an attack and in remission. Methods: 20 FMF patients, who were naive to colchicine treatment and did not have amyloidosis, and 10 patients with Behçet’s disease (BD) were enrolled in this study. Phagocytosis, respiratory burst, CD11a/CD18 expression and intracellular cytokine synthesis were determined by flow cytometry. Endotoxin tolerance in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
0

Year Published

2008
2008
2014
2014

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(22 citation statements)
references
References 94 publications
1
21
0
Order By: Relevance
“…Previously, we had found that colchicine is able to restore impaired LPS-homologous tolerance induction (assayed by flow cytometry of monocytes, intracellularly synthesizing TNF-α), in FMF patients upon increasing the intracellular IL-4 synthesis and monocyte "alternative" activation [9]. In this study we observed that colchicine increased both IL-10 and IL-1β production by monocytes obtained from ND and FMF patients.…”
Section: Discussionsupporting
confidence: 52%
See 2 more Smart Citations
“…Previously, we had found that colchicine is able to restore impaired LPS-homologous tolerance induction (assayed by flow cytometry of monocytes, intracellularly synthesizing TNF-α), in FMF patients upon increasing the intracellular IL-4 synthesis and monocyte "alternative" activation [9]. In this study we observed that colchicine increased both IL-10 and IL-1β production by monocytes obtained from ND and FMF patients.…”
Section: Discussionsupporting
confidence: 52%
“…Endotoxin tolerance was monitored by measuring the production of IL-1β, IL-10, IFN-γ and TNF-α by monocytes in response to LPS after preincubation in the presence or absence of two doses of LPS [9]. Monocytes at 5 ×10 5 cells/ml density were cultured for 18 h in the presence or absence of 100 ng/ml LPS or either with 2 μg/ml colchicine or 2.5 μg/ml PGN or 5 μg/ml MDP or 10 ng/ml recombinant IL-4.…”
Section: Endotoxin Tolerancementioning
confidence: 99%
See 1 more Smart Citation
“…Although we ascertained that increased endotoxin sensitivity in an attack-free period could be a result of a shift in monocyte activation program from "alternatively'' into ''classically" activated [22], the precise mechanisms that could explain aberrant endotoxin tolerance and resolution of infl ammation in FMF are entirely unknown. According to the dynamic view of monocyte activation that integrates cell capacity to switch from one activated state to another, a shift in monocyte activation program may cause resolution of infl ammation without new monocyte recruitment into the infl ammatory site [23].…”
Section: Introductionmentioning
confidence: 99%
“…Here we investigated homologous and heterologous endotoxin tolerance induction and endotoxin-induced monocyte apoptosis in FMF patients during attack and attack-free periods using the whole blood cell culture technique that preserves blood microenvironment, reduces the risk of contamination, pre-activation, or selective depletion or enrichment of cell subsets [22]. We also used a pharmacological approach to study effects of colchicine (Col) and iodine-lithium-adextrin (ILaD) upon FMF monocytes, as our earlier studies revealed their high potential for inducing homo-and crossendotoxin tolerance and intracellular cytokine synthesis polarization of monocytes during Behçet's disease [25].…”
Section: Introductionmentioning
confidence: 99%